Thermal Performance on Tapering Heat Pipe - ., Sarip; ., Sudjito; Yuliati, Lilis; Agus Choiron, Moch. (International Journal of Engineering and Technology, 2019)
Various design of heat pipes had been developed in previous research to enhance thermal performance. In this study, tapering heat pipe is developed. The method used true experimental to observe temperature distribution in the heat pipe. Geometric design is set as the ratio of diameter evaporator (d) and condenser (D) which are d/D =1/1, 1/2, 1/3 and 1/4. Heat source (Q) is varied by using DC power supply of 25, 30, 35, 40, 45 and 50 Watt. The temperature was measured by using k-type thermocouple with NI-9211 and c-DAQ 9271 module. Wick heat pipe is set as screen mesh with 56,5 Âµm wire diameter with one single layer. Wick screen mesh material used is stainless steel with 40 W/(mâ€¢K) thermal conductivity on layer shape. Thermal resistance decrease, high evaporation time, and stable temperature distribution are an indicator performance to determine the best thermal performance. Based on the results, it can be denoted that d/D and Q affected to thermal performance difference. Both of d/D and Q increased, thermal performance increases. The tapering heat pipe with d/D = 1/4 and Q = 50 Watt provide the better thermal performance.Â